Features of the operation of the heat exchanger-condenser of modern passenger aircraft - Chichindaev Alexander; Khromova Irina; Vyborov Maxim (EPJ Web of Conferences)
This paper presents a description of the design problems of the heat exchanger-condenser of modern aviation air conditioning systems (ACS) of passenger aircraft. The purpose of the work is to study known design methods and explore an alternative option. The paper presents a description of the problems of operating an ACS heat exchanger-condenser: freezing of the heat transfer surface along the cold and hot paths, as well as known methods of anti-icing systems (AIS) for it. The features of the calculation and design of the design variant under study are described. The results of computer simulation of heat transfer processes for various configuration options of the heat exchanger-condenser are presented. The most effective ways to prevent surface freezing are shown. The work is based on original copyright materials obtained at the Department of Technical Thermophysics of NSTU.